Colorimetric indicator based on chitosan/gelatin with nano-ZnO and black peanut seed coat anthocyanins for application in intelligent packaging - Lu, Min; Zhou, Qi; Yu, Hui; Chen, Xiaoe; Yuan, Gaofeng (Food research international, 2022)
Chitosan/gelatin based intelligent pH-sensing indicator film was fabricated by incorporating zinc oxide nanoparticles and black peanut seed coat anthocyanins, and was used to monitor the freshness of shrimp at 4 °C. A distinctive color change of the film was consistent with the rising trend of TVB-N in shrimp. [Display omitted] •Chitosan/gelatin films incorporating nano-ZnO and black peanut seed coat anthocyanins were developed.•The films showed good antioxidant and antibacterial activities.•Anthocyanins improved the UV barrier and mechanical properties.•The films exerted good pH-sensing color-change properties.•The films have a high potential for monitoring the freshness of shrimp. Chitosan/gelatin (CG) based intelligent pH-sensing indicator films were fabricated by incorporating zinc oxide nanoparticles (nano-ZnO) (CGZ) and different amounts of black peanut seed coat anthocyanins (BPCSA) (CGZ-h). Chitosan/gelatin showed good compatibility with anthocyanins and nano-ZnO, and the addition of nano-ZnO and BPSCA did not affect the original crystal structure of films. Addition with BPSCA simultaneously increased the tensile strength and elongation at break of CGZ-h films. BPSCA decreased the water vapor permeability, whereas they increased the UV barrier property of the CGZ-h films. CGZ-h films exerted strong antioxidant and antibacterial activities, which mainly attributed to the BPSCA and nano-ZnO, respectively. CGZ-h films presented good pH-sensing color-change properties in different buffer solutions. The CGZ-h2 film was used to monitor the freshness of shrimp at 4 °C. The result showed that distinctive color change of the CGZ-h2 film was highly correlated with the change of the total volatile basic nitrogen, pH and total viable count of shrimp. These results revealed the potential application of CGZ-h for real-time monitoring the freshness of food.